Making sense of organizational learning : putting theory into practice - Kirwan, Cyril (Gower, 2013)
The ability of a business to learn is becoming increasingly important for success. In Making Sense of Organisational Learning, Cyril Kirwan examines the wide range of factors necessary to create and sustain organisational learning and knowledge at all levels. The book shows how to best exploit the knowledge that already exists within the organisation while at the same time develop the capability of the people that work there, highlighting in particular the role of the HR function and of line managers. Each chapter provides theoretical background and real-world examples. Diagnostic questionnair.